PROSEDUR AUDIT KAS DAN SETARA KAS PADA PT. LDR OLEH KANTOR AKUNTAN PUBLIK AU & REKAN - Rizka Zahrotul Zahna, (2022)
Au & Partners Public Accountant firm is KAP that has been licensed by the Minister of Finance and registered with the Financial Services Authority (OJK) to provide services in the field of general audit such as auditing financial statements against one of KAP AU & Rekan's clients, namely PT. LDR engaged in engineering consultants. Cash and cash equivalents are liquid assets and are almost used in every transaction, which makes cash and cash equivalents very important for the company. Because of this nature, cash and cash equivalents can have the potential for misappropriation and abuse. Thus, it is necessary to hold an examination by an independent auditor of cash and cash equivalents that have been presented in the financial statements. This report aims to determine the procedures for auditing cash and cash equivalents at PT. LDR by KAP AU & Rekan. Based on the audit results, it shows that all cash records and cash equivalents have been carried out reasonably in all material matters.